HOAX DAN FENOMENA KEBEBASAN BERPENDAPAT DI ZAMAN HOMO DIGITALIS - Mikha Mikha; Wanni Payung Tasik, Naomi Nelsa Padidi, Efendi Desayo, Baso' Taruk lawa (Jurnal Komunikasi, 2023)
Democracy that prevails in Indonesia does not only have an impact and influence on the Indonesian government system. The presence of Human Rights as a rule also plays a role in Indonesia’s constitutional democratic system, which of course also affects every individual. Freedom of expression and opinion is one form of the presence of human rights, which is the reason for the presence of media freedom recently. Along with its development, the media has undergone many changes, which were previously only in print and conventional forms such as newspapers, television, magazines, newspapers and or radio, but now have evolved to the presence of social media which makes it easier as well as an alternative for humans to access information. But on the other hand, despite having the advantage of the presence of social media in this technological era, social media has also turned out to be a threat not only to the younger generation, but at all human ages. One thing that has become a hot topic of discussion with the presence of digital media is the freedom of humans to express opinions, which is often fake news (hoax). This phenomenon is also one of the main causes of the emergence of racism and hate speeches from one religion to another, ethnicity between tribes, ethnicity between ethnicities, and many more. Law enforcement alone is not considered capable enough to overcome the hoax problem that is developing in the wider community. It takes awareness and firmness of attitude and character of citizens in using social media with the aim of maintaining the integrity of society, especially the integrity of the Indonesian nation. Consistency and awareness is meant by applying the principle of filtering before sharing, protecting the rights of other individuals, strictly separating private and public needs, and fully acknowledging that the cultural diversity of the community is a sensitive matter. Things like that are believed to be able to protect human existence (Homo sapiens) from the phenomenon of freedom of opinion that leads to hoaxes in this digitalization era (Homo Digitalis).